Pengaruh Moralitas Individu, Religiusitas dan Budaya Etis Organisasi Terhadap Kecurangan (Fraud) Akuntansi pada Lembaga Perkreditan Desa Di Kecamatan Abiansemal Kabupaten Badung - Ni Luh Heppy Monika Santya Dewi; Putu Cita Ayu; Ni Komang Sumadi (UNHI Press, 2022)
Fraud is an act done intentionally by someone whose impact can be detrimental to many parties. In this study, we will discuss the relationship between a person's morals, religiosity, and organizational culture that can affect fraud in organizations. LPD (Village Financial Institution) employees in Abiansemal District were used as the research population and 99 of them were used as samples. In this study, multiple regression analysis was used as a research technique by looking at the direct relationship formed between the independent variables on fraud.